Glycoconjugation of Betulin Derivatives Using Copper-Catalyzed 1,3-Dipolar Azido-Alkyne Cycloaddition Reaction and a Preliminary Assay of Cytotoxicity of the Obtained Compounds - Mirosława Grymel; Gabriela Pastuch-Gawołek; Anna Lalik; Mateusz Zawojak; Seweryn Boczek; Monika Krawczyk; Karol Erfurt (Molecules, 2020)
Pentacyclic lupane-type triterpenoids, such as betulin and its synthetic derivatives, display a broad spectrum of biological activity. However, one of the major drawbacks of these compounds as potential therapeutic agents is their high hydrophobicity and low bioavailability. On the other hand, the presence of easily transformable functional groups in the parent structure makes betulin have a high synthetic potential and the ability to form different derivatives. In this context, research on the synthesis of new betulin derivatives as conjugates of naturally occurring triterpenoid with a monosaccharide via a linker containing a heteroaromatic 1,2,3-triazole ring was presented. It has been shown that copper-catalyzed 1,3-dipolar azide-alkyne cycloaddition reaction (CuAAC) provides an easy and effective way to synthesize new molecular hybrids based on natural products. The chemical structures of the obtained betulin glycoconjugates were confirmed by spectroscopic analysis. Cytotoxicity of the obtained compounds was evaluated on a human breast adenocarcinoma cell line (MCF-7) and colorectal carcinoma cell line (HCT 116). The obtained results show that despite the fact that the obtained betulin glycoconjugates do not show interesting antitumor activity, the idea of adding a sugar unit to the betulin backbone may, after some modifications, turn out to be correct and allow for the targeted transport of betulin glycoconjugates into the tumor cells.